PERFORMANCE ESTRATÉGICA Y ECONÓMICA DE EMPRESAS ESTATALES: EL CASO DE LAS AEROLINEAS LATINOAMERICANAS - Gallegos Monteagudo, Armando (1992)
Seeks to develop new methods to identify objectives and evaluate the performance of state-owned companies, as well as to compare their performance with that of private companies. Comprises the operations between 1981 and 1987 of 17 airlines classified as: public Latin American, private Latin American and North American with operations in Latin America. First, the Delphi method is applied to identify the objectives and criteria for evaluating the performance of public airlines. Secondly, new methods for performance evaluation are evaluated using Data Envelopment Analysis. The third part is devoted to comparative performance studies and their implications for management and public policy formulation; the tools developed in the previous stages are used to relate ownership, international competition and efficiency. The results of the study indicate that the privatization strategies applied may produce some, but modest, efficiency gains. More fruitful might be to consider other strategies that allow moving up the entire efficiency frontier, such as some deregulation of domestic and international markets.